Analisis Muatan Life Skill Dalam Program Komunitas CreSHome (Creative, Smart, and Homey Community) - Jubaidah, Jubaidah; Diba, Adinda Farah; Saputri, Arum Dwi; Amenobelia, Amenobelia; Anysa, Ega; Almarind, Marisa; Syahputri, Nurlaily; Rasenda, Rasenda; Yolanda, Yolanda; Thomas, Thomas (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2025)
CreSHome is a youth community that actively develops the capacity of its members through various activities such as Legislative School, Political School, Leadership Program, visits to the North Sumatra Library, the 3rd Anniversary celebration, and Town Hall Meetings. This research focuses on four aspects of life skills, namely personal skills, social skills, academic skills, and vocational skills. The aim of this research is to analyze what life skills are contained within the CreSHome community through the programs implemented by the CreSHome community. This research employs a descriptive qualitative approach. The research subjects were selected using purposive sampling techniques with a total of 25 participants. Data collection was conducted through direct observation and in-depth interviews. Data analysis was performed descriptively on all research data. The analysis results indicate that CreSHome programs significantly contain and develop these skills. These findings provide important insights for the development of non-formal education-based communities to foster the life skills of the younger generation in a holistic manner